Fakultas Ekonomika dan Bisnis, Universitas Negeri Semarang - Putri Malasari; Alan Mustapa; Muhammad Khusen; Jarot Tri Bowo Santoso (Universitas Negeri Makassar, 2026)
Abstrack. This study aims to explore students’ perceptions of using a Card learning game as a gamified learning medium in teaching monetary policy in economics education. The research employed a descriptive qualitative approach with a case study design. The study was conducted during the 2024/2025 academic year at a public senior high school in Semarang, involving twelfth grade students who participated in economics learning activities using the card based learning media Bank Indonesia Smart Move. Participants were selected purposively based on their active involvement in the learning process and willingness to share their experiences. Data were collected through semi structured interviews supported by field notes. Data analysis was carried out using thematic analysis to identify key themes derived from students’ learning experiences and perceptions. The findings indicate that the Card learning game was perceived to enhance student engagement, learning motivation, and understanding of monetary policy concepts through interactive and contextual learning activities. Nevertheless, some students reported the need for additional explanation and reinforcement after the game sessions to support deeper conceptual understanding.Keywords: Students’ perceptions; card learning game; gamified learning; economics learning; monetary policy. Abstrak. Penelitian ini bertujuan untuk menganalisis persepsi siswa terhadap penggunaan Card learning game sebagai media pembelajaran yang digamifikasi pada materi kebijakan moneter dalam pembelajaran ekonomi. Penelitian menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Penelitian dilaksanakan pada tahun ajaran 2024/2025 di Sekolah Menengah Atas Negeri 12 Semarang dengan subjek penelitian siswa kelas dua belas yang mengikuti pembelajaran ekonomi menggunakan media kartu pembelajaran Bank Indonesia Smart Move. Pemilihan partisipan dilakukan secara purposive dengan melibatkan siswa yang aktif mengikuti pembelajaran dan bersedia memberikan informasi secara mendalam. Data dikumpulkan melalui wawancara semi terstruktur yang didukung dengan catatan lapangan. Teknik analisis data menggunakan analisis tematik untuk mengidentifikasi tema utama berdasarkan pengalaman dan pandangan siswa. Hasil penelitian menunjukkan bahwa penggunaan Card learning game dipersepsikan mampu meningkatkan keterlibatan belajar, motivasi, dan pemahaman konsep kebijakan moneter melalui aktivitas pembelajaran yang lebih interaktif dan kontekstual. Namun demikian, beberapa siswa masih memerlukan penguatan materi dan pendampingan setelah kegiatan permainan agar pemahaman konsep dapat terbentuk secara lebih mendalam.Kata Kunci: Persepsi siswa; card learning game; gamifikasi pembelajaran; pembelajaran ekonomi; kebijakan moneter